Peningkatan Keterampilan Menulis melalui Media Youtube - Aldiitya; Saputra, Alditya Arya; Sudrajat, Yayan (PT. LANCAR MEDIA KOMUNIKASI, 2022)
This study aims to describe the benefits of YouTube learning media in teaching Indonesian language Explanatory Text material for class XI at SMK PKP 1. This research uses a qualitative descriptive approach. Qualitative descriptive research is research that seeks to describe a symptom, event, event that has occurred now. The subjects of this study were 22 students of class XI-MultiMedia. The object of this research is the use of YouTube videos on the Arisa Nur Aini channel in learning explanatory text material. The results of the research can be seen in the results of the tests carried out in the teaching and learning process conducted in class XI-MultiMedia SMK PKP 1. On the test results students obtained an average score of 88.27 in the good category. Evidenced by the number of students as many as 15 students scored above the KKM and 7 students scored below the KKM.